A PES framework coupling socioeconomic and ecosystem dynamics from a sustainable development perspective. (1st March 2023) - Li, Fufu; Liu, Hongyan; Wu, Shaohua; Wang, Yanhui; Xu, Zhenci; Yu, Pengtao; Yan, Daohao
Abstract: Payments for ecosystem services (PES) are becoming a global ecological protection strategy used to promote sustainable social and economic development. However, the current PES research and applications are often local and one-sided. The lack of a unified framework for PES results in a high policy cost and low ecological and social benefits. A large number of local PES experiences need to be comprehensively analyzed to construct a unified PES framework, which can provide support for the implementation and optimization of nature conservation policy in different regions of the world. Here, we combined natural language processing methods to analyze 1919 global studies on PES. We obtained the topics and spatiotemporal distributions of PES, as well as the compensation modes of hotspot ecosystem services in 114 countries worldwide. PES have been studied in 80% of the world (excluding Antarctica), but the research topics and distributions are very uneven. We found a disconnection between PES socioeconomic strategies and knowledge of natural ecosystem dynamics. Therefore, the knowledge and experience of PES must be exchanged globally, and PES need to be further integrated with the sustainable development goal (SDG) framework. We propose a PES framework that couples socioeconomic and ecosystem dynamics and be oriented toward sustainable development to make comprehensive management decisions. On this basis, a consistent PES solution may be provided for future theoretical research and implementation strategies of conservation. Highlights: Literature mapping of 15 categories of PES topics in 114 countries around the world was conducted. PES modes for water supply, carbon sequestration, and biodiversity conservation in different countries were reviewed. A disconnection exists between PES socioeconomic strategies and knowledge of natural ecosystem dynamics. Oriented to sustainable development, a PES framework coupling socioeconomic and ecosystem dynamics was proposed.